Changes in breakdown pressure and fracture morphology of sandstone induced by nitrogen gas fracturing with different pore pressure distributions. (September 2018) - Hou, Peng; Gao, Feng; Gao, Yanan; Yang, Yugui; Cai, Chengzheng
Abstract: To better understand effect of pore pressure distribution on fracturing behavior of reservoir rocks in gas fracturing, four types of pore pressure distribution were designed by considering the seal method of sample and the gas injection rate; i.e., no gas invasion, gas filtration (0.075 MPa/s), gas filtration (0.2 MPa/s) and no gas filtration. Nitrogen gas fracturing experiments were performed on cylindrical cores of the sandstone, and the breakdown pressure and macroscopic/microscopic fracture morphology of the sandstone sample were analyzed. The results show that the breakdown pressure of the sandstone reduces in the following order: no gas invasion, gas filtration (0.2 MPa/s), gas filtration (0.075 MPa/s), and no gas filtration. In the same gas injection rate, the breakdown pressure value of the sample in no gas filtration case decreases by 69.98% and 45.6% in comparison no gas invasion and gas filtration case, respectively. The rupture degree of the sandstone and the complexity of the induced fracture morphology are highest in no gas filtration. The macroscopic damage degree of the sample is minimum in gas filtration, but the complexity of the induced fracture morphology is higher in gas filtration than that in no gas invasion. The above results indicate that converting fracturing with external load into fracturing with fluid pressure in pores and fracture is an effective way to reduce the breakdown pressure of the sandstone and generate complex multi-fractures network in gas fracturing. Highlights: Effect of pore pressure distribution on the failure of the sandstone is studied in nitrogen gas fracturing. Improving pore pressure distribution can decrease breakdown pressure of the sandstone. Increasing instability of internal structure of the sandstone is helpful to produce complex fracture.